2021
DOI: 10.21037/apm-20-1742
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of malignant eosinophilic pleural effusion: incidence, etiology and prognostic significance

Abstract: Eosinophilic pleural effusion (EPE) is defined as a pleural fluid with an eosinophilic count exceeding 10% and currently considered to be mainly caused by malignancy. However, the incidence, etiology and prognostic significance of malignant eosinophilic pleural effusion (MEPE) have not been studied extensively yet. Thus, the objective of this review was to summarize medical studies regarding MEPE to 2020 throughout an extensive search of PubMed. Overall, MEPE was a disease associated with multiplecytokines-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Wysenbeek's study showed that the aetiologies of EPE were trauma (39%), congestive heart failure (14%), infection (8.5%) and idiopathic effusion (8.5%) [9]. The differences in results may be explained by the different prevalences of the aetiology of PE at some institutions [10]. Although there was no drug-induced EPE in our study, the list of possible aetiologies has been increasing in recent years, including methimazole, carbimazole, valproic acid, mesalamine, olanzapine and others [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Wysenbeek's study showed that the aetiologies of EPE were trauma (39%), congestive heart failure (14%), infection (8.5%) and idiopathic effusion (8.5%) [9]. The differences in results may be explained by the different prevalences of the aetiology of PE at some institutions [10]. Although there was no drug-induced EPE in our study, the list of possible aetiologies has been increasing in recent years, including methimazole, carbimazole, valproic acid, mesalamine, olanzapine and others [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review study conducted by Li and his colleagues found malignancy to be the commonest cause of EPE [7], and its incidence has a close relationship with the population being studied and the diagnostic criteria being used. Among the causes of malignant EPE, lung cancer was found to be the leading cause with 23 reported cases, followed by non-Hodgkin lymphoma and metastatic carcinoma of unknown origin, each comprising 5% of total reported cases of malignant EPE [7]. Hodgkin's lymphoma is a rare cause of malignant EPE with only two reported cases [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…An overwhelming number of recently published studies have demonstrated that the prevalence of malignancy could be as frequent in EPEs as in non-EPEs and that there is no statistically significant difference in the incidence of malignant neoplasm between the two [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations